2011
DOI: 10.1007/s10588-011-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based approach for structured modeling, analysis and improvement of safety culture

Abstract: Safety culture is broadly recognized as important for operational safety in various fields, including air traffic management, power plant control and health care. Previous studies addressed characterization and assessment of safety culture extensively. Nevertheless, relations between safety culture and formal and informal organizational structures and processes are yet not well understood. To address this gap, a new, formal, agent-based approach is proposed. This paper shows the application of the approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The ABM method has gradually been applied to the field of construction safety management. Sharpanskykh and Stroeve [62] proposed a new, formal, agent-based approach to study the relations between safety culture and formal and informal organizational structures and processes. Choi et al [39] used an ABM method to study management norms, workgroup norms, and the relationship between security attitudes and unsafe behavior.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…The ABM method has gradually been applied to the field of construction safety management. Sharpanskykh and Stroeve [62] proposed a new, formal, agent-based approach to study the relations between safety culture and formal and informal organizational structures and processes. Choi et al [39] used an ABM method to study management norms, workgroup norms, and the relationship between security attitudes and unsafe behavior.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…TTL has proven to be a suitable formal language for the specification of agent-based models of complex sociotechnical systems (Bosse et al 2009;Sharpanskykh and Stroeve 2011;Sharpanskykh 2011). TTL is a variant of an order-sorted predicate logic (Manzano and Manzano 1996).…”
Section: Formal Modeling Languagementioning
confidence: 99%
“…The SD models illustrated safety management theories based on major accidents. The agent-oriented SD model (Feola et al, 2012) and ABS (Sharpanskykh and Stroeve, 2011) were more practical and were focused on evaluation of safety interventions. A detailed review of the six papers can be found in (Goh and Palak, 2014).…”
Section: Simulation and Safety Managementmentioning
confidence: 99%
“…The factorial experiment is meant to guide managers in identifying impactful interventions and the interactions between factors (or controllable variables). Despite its importance, none of the six safety simulation papers reviewed (Rudolph and Repenning, 2002;Cooke, 2003;Cooke and Rohleder, 2006;Salge and Milling, 2006;Sharpanskykh and Stroeve, 2011;Feola et al, 2012) conducted factorial experiments. A 2 k factorial design is performed herein to encourage its usage when utilizing the proposed framework.…”
Section: Factorial Experimental Designmentioning
confidence: 99%